Exploring the Impact of Peer Interaction and Self-Efficacy on Students' Engagement in Online Learning - Septiana Sari; Suryadi (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2025)
Abstract This study investigated the impact of peer interaction and self-efficacy on student engagement in online learning among 100 tenth-grade students at SMAN 1 Mancak, Serang, Banten, Indonesia. The primary objective was to explore the influence of peer interaction and self-efficacy on students' engagement in online learning environments. Specifically, the study aimed to determine the extent to which peer interaction influences student engagement, how self-efficacy affects student engagement, and whether these two factors jointly predict levels of student engagement. Employing a quantitative survey design and multiple linear regression analysis, the research examined the individual and combined effects of these variables on students' behavioral, emotional, and cognitive engagement in virtual learning environments. The findings revealed a strong positive correlation between peer interaction and self-efficacy with student engagement (R = 0.722, R2 = 0.521). Both peer interaction (B = 0.481, p < 0.001, β = 0.418) and self-efficacy (B = 0.402, p < 0.001, β = 0.404) independently and significantly predicted student engagement, with nearly equal relative contributions. These results underscore the critical roles of both social connections and individual beliefs in one's capabilities in fostering active participation in online learning. The study highlights the importance of designing online learning environments that facilitate meaningful peer interactions and enhance students' self-efficacy to improve overall engagement and learning outcomes.